Factor structure of the Japanese version of the Quality of Life in Alzheimer's Disease Scale (QOL‐AD). Issue 1 (24th April 2019) - Yamada, Takahiro; Nakaaki, Shutaro; Sato, Junko; Sato, Hirofumi; Shikimoto, Ryo; Furukawa, Toshi A.; Mimura, Masaru; Akechi, Tatsuo
Abstract : Background: The Quality of Life in Alzheimer's Disease Scale (QOL‐AD) developed by Logsdon et al. in1999 is believed to be useful for evaluating responses from both patients and their caregivers. We previously confirmed both the reliability and the validity of the Japanese version of the QOL‐AD. However, the factor structure of this scale should be confirmed because the QOL‐AD covers multiple facets of dementia patients' lives. Thus, we performed a factor analysis of the Japanese QOL‐AD. Then, we examined the correlations between each of the identified QOL factor scores and the results of other scales. Methods: The Japanese version of the QOL‐AD was given to 132 AD patients and 132 caregivers. Four other tests were also performed at the same time: the Mini‐Mental State Examination, the Neuropsychiatric Inventory (NPI), the Hyogo Activities of Daily Living Scale (HADL), and the Short Memory Questionnaire. A factor analysis using Varimax rotation was used to examine the dimensions underlying the QOL‐AD. In addition, we examined the Pearson correlations between each of the identified QOL factor scores and the results of the other four tests. Results: Factor analyses of both versions of the Japanese QOL‐AD (both the patients' and the caregivers' responses) revealed three factors that were named 'psychological wellbeing', 'human relationships', and 'physical and social environment'. The 'psychological wellbeing' factor was significantly correlated with the Mood factor of the NPI. The 'human relationships' factor was significantly correlated with the Psychosis factor of the NPI. The 'physical and social environment' factor was significantly correlated with the HADL. Conclusions: Both the patients' and the caregivers' responses to the Japanese version of the QOL‐AD were composed of three factors: 'psychological wellbeing', 'human relationships', and 'physical and social environment'. The present results support the multi‐domain concept of QOL proposed by Lawton.